(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Aim: To evaluate the thyroid status in infertile women. Materials and methods: A cross sectional study was conducted in the department of Infertility of Bangabandhu Shaekh Mujib Medical University from January 2012 to December 2012. A total 400 patients of infertility were studied. The thyroid function status of the subjects were assessed and analyzed. Results: Of the 400 women enrolled for the study, 221(55%) patients with primary infertility and 179 (45%) patients were with secondary subfertility. The mean age of the responders were 22.3±4.6 years, the mean duration of marriage were 4.5±1.2 years and mean BMI were 23.2±3.1 kg/m2.Among the 400 patients 70.50% that is 293 patients were euthyroid, TSH level was increased in 23% or in 92 subjects. Depending upon the TSH levels, hypothyroid infertile women were further subdivided into subclinical hypothyroidism where TSH 46 mIU/L with normal FT4 (9-24 pmol/L) and clinical hypothyroidism where TSH > 6 mIU/L with raised FT4 level. It was found that 66 (71.74%) of hypothyroid infertile women were with subclinical and remaining 26 (28.26%) were with clinical hypothyroidism.Hyperthyroidism that is low TSH level (<.5 mIU/L) found in 15(3.75%) subjects and visible goiter was present in only 2 patients. In 96 hypothyroid infertile females, the mean TSH levels were 7.34 ± 2.13 mIU/L, and mean FT4 level was 17.34±3.23pmol/L. The mean PRL levels were 52.46 ±11.17 ng/ml. Conclusion: Thyroid dysfunction is an important factors for infertility. Early diagnosis and timely intervention can reduce the burden of infertility due to thyroid dysfunction. J Bangladesh Coll Phys Surg 2014; 32: 206-210